D(1) Receptor in Interneurons of Macaque Prefrontal Cortex: Distribution and Subcellular Localization - Muly, E. Chris (J Neurosci, 1998)
Working memory performance is influenced by dopamine activation of D1 family dopamine receptors in the prefrontal cortex; working memory performance is maximal at moderate stimulation of D1 family receptors and is reduced by either higher or lower levels of D1 stimulation. The neuronal mechanisms that underlie this complex relationship are not yet understood. Previous work from this laboratory has demonstrated that the D1 family receptors, D(1) and D(5), are located in different compartments of pyramidal cells. Here we use an antibody specific to the D(1)receptor and double-label immunohistochemistry at the light and electron microscopic level to demonstrate that D(1)-like immunoreactivity (D(1)-LIR) is also present in interneurons. D(1) receptor is prevalent in parvalbumin-containing interneurons and is less common in calretinin-containing interneurons. At the ultrastructural level, D(1)-LIR is found associated with the Golgi apparatus and endoplasmic reticulum in the soma, with the membranes of vesicles in proximal dendrites, and with the plasma membrane on distal dendrites, where it is often located near asymmetric synapses. In addition, D(1)-LIR is also seen in presynaptic axon terminals, which give rise to symmetric synapses onto dendritic shafts and soma. These results raise the possibility that the circuit basis of working memory in the prefrontal cortex involves a D(1)-mediated inhibitory component.